Cyfrowy ijtihad. Strategia Musawah Movement w kształtowaniu świadomości społecznej - Dworska, Żaklina (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
This paper examines the impact of digital ijtihad employed by the Musawah organisation on the transformation of Muslim family law, demonstrating how the reinterpretation of religious norms contributes to the emancipation of women. Despite the extensive research conducted on the hermeneutics of Islamic texts, there is a paucity of attention paid to the digital political communication strategies employed online. The objective of this study was to ascertain the mechanisms that shape emancipatory narratives by Musawah and their influence on the redefinition of gender roles within traditional legal frameworks.
Keywords: ijtihad; Ruch Musawah; prawa kobiet; komunikacja polityczna; media masowe; Musawah Movement; women`s rights; political communication; mass media